Les déplacements identitaires d’enseignantes formées à l’étranger s’intégrant dans l’école montréalaise - Joëlle Morrissette; Didier Demazière (Éducation et Socialisation)
Many foreign-trained teachers continue their careers in the province of Quebec, due to the current labor shortage in this area. For those coming from very different countries, the first experiences are such a big shock that they initiate an identity transformation. Based on individual and group interviews with 4 of them, analyzed from an interactionist perspective, a research led to identify of three changes in their “relationship with oneself”: from the knowledge master to the educational relationship specialist, from the monitored technician to a more autonomous professional, from the competitor who stands out from the crowd towards a cooperative peer who complies. These identity shifts highlight the ways in which interactions at work have socialized the participants at a coherent vision of teaching in Quebec school by reproducing prevailing professional conventions.